The evolution of collaborative networks: A social network analysis of Chinese environmental protection policy. (January 2023) - Li, Yanwei; Huang, Jing
Interagency collaboration helps governments to better resolve various complex societal problems. This contribution examines the mechanisms underlying the collaboration of disparate national government agencies engaged in Chinese environmental protection. We test three dominant mechanisms, namely, the institutionalization of collaborative networks, resource interdependence and exchange, and preferential attachment. It is concluded that a collaborative network over time becomes cohesive, that national government agencies prefer to collaborate with popular agencies and tend to collaborate with those whose resources are different from their own, and that popular agencies tend to maintain their core positions over time. Our study enriches the current governance and policy literature through adding building blocks for the evolution of collaborative network and network partner selection.